The Y Plan Countdown : A Great New Shape in 36 Days - Mowbray, Lesley and Gaskell, Jill (London Hamlyn, 1992)
The Y plan 36 day countdown was developed from the feedback from the original Y plan. The countdown is a progressive programme with three colour coded levels. It concentrates predominantly on improving body shape and tone.
Include Color Illustration
Keywords: Physical fitness